2006
DOI: 10.1007/s11912-006-0030-8
|View full text |Cite
|
Sign up to set email alerts
|

Second-line treatment of small-cell lung cancer

Abstract: Approximately 45,000 new cases of small-cell lung cancer were diagnosed in 2005 in the United States. Although response to first-time therapy is up to 90%, the majority of patients will ultimately relapse. Therefore, active second-line therapy is needed for this patient population. The only second-line treatment for small-cell lung cancer approved by the US Food and Drug Administration is topotecan. Other agents have been investigated and have shown modest efficacy. These include vinorelbine, irinotecan, etopo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
7
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 27 publications
(23 reference statements)
0
7
0
Order By: Relevance
“…However, the only second-line treatment for SCLC approved by the US Food and Drug Administration (FDA) is topotecan [30,31]. Several studies have evaluated potential alternatives to topotecan in this indication.…”
Section: Discussionmentioning
confidence: 99%
“…However, the only second-line treatment for SCLC approved by the US Food and Drug Administration (FDA) is topotecan [30,31]. Several studies have evaluated potential alternatives to topotecan in this indication.…”
Section: Discussionmentioning
confidence: 99%
“…Irinotecan has international regulatory approval for use in the treatment of colorectal cancer and is active against a wide variety of solid tumors. [1][2][3][4][5] Much is known about the drug's metabolism and pharmacokinetics. The hydrolysis of irinotecan by the high-affinity carboxylesterase-2 is responsible for activation of irinotecan to SN-38 (7-ethyl-10-hydroxycamptothecin), a potent topoisomerase I inhibitor.…”
mentioning
confidence: 99%
“…Clinical studies have shown that no therapy significantly improved the 15–20% response rate (RR) provided by second-line topotecan (the only drug with official approval in second line). Topotecan proved its efficacy regarding patients' response to therapy, safety, and symptom palliation in many phase II studies [11, 12]. The randomized multicenter phase III study on topotecan versus cyclophosphamide, doxorubicin, and vincristine (CAV) in patients with SCLC who progressed at least 60 days after completion of first-line therapy showed that topotecan was at least equally effective as CAV and led to its approval by the FDA [11, 12].…”
Section: Introductionmentioning
confidence: 99%